Correlation of hair risperidone concentration and serum level among patients with schizophrenia. Issue 1 (20th February 2019) - Sun, Xiujia; Wang, Lihua; Yang, Fuzhong; Ren, Juanjuan; Jiang, Ping; Liu, Hongmei; Li, Huafang; Li, Chunbo; Zhang, Chen
Abstract : Background: Risperidone (RSP) has a rapid onset in vivo, low dosage and high plasma protein binding rate, therefore therapeutic drug monitoring (TDM) is needed to ensure safety in clinical treatment. However, compared with blood, hair is non-invasive, safe, non-infectious and easy to transport and store. Aims: This study aims to investigate the correlations among the drug concentrations of RSP in hair and serum, which provides an experimental basis to explore hair as a novel biomaterial to meet the needs of clinical detection. Methods: 34 patients with schizophrenia treated with RSP for more than 3 months were enrolled in this study. About 1 cm section of hair near the scalp was taken from the subjects, pretreated and detected by liquid chromatography-mass spectrometry. A correlation analysis was conducted among the drug concentrations in hair, the serum concentrations and the daily dosage. The data were analysed using SPSS 20.0 software. Results : There was significant correlation between the hair concentration of RSP (two-tailed test, r=0.440, p =0.009) with the serum concentration of RSP, and the hair concentration of 9-hydroxyrisperidone (9-HR) with the serum concentration of 9-HR had no significant correlation (two-tailed test, r=−0.217, p =0.217); the total concentration of the RSP and 9-HR had no significant correlation between hair and serum (r=0.227, p =0.196). The dosage had no statistically significant correlation with the concentration of RSP in hair (r=0.207, p =0.241), 9-HR in hair (r=−0.194, p =0.271) and the total concentration of RSP and 9-HR in hair (r=0.188, p =0.288). There was no statistical correlation between the dosage and the concentration of RSP in serum (r=−0.059, p =0.741), but significant correlation between the dosage and 9-HR in serum (r=0.581 p <0.001) was found, and the correlation between the dosage and the total concentration of the two drugs RSP and 9-HR in serum was also significant (r=0.437, p =0.01). Conclusion: The correlation analysis showed that the concentration of RSP in hair was statistically significant with the serum RSP concentration. In this study, we provided some experimental basis for hair as a new biomaterial to monitor the therapeutic drug concentration.